Green Accounting Impact on Profitability in Mining Companies Listed in Indonesia Stock Exchange - Sululing, Siswadi; Dako, Aulia; Teri, Teri (Magister Akuntansi - Universitas Atma Jaya Makassar, 2024)
The aim of the research is to analyze the effect of green accounting to profitability on mining company listing in Indonesia Stock Exchange. Sample is 20 mining companies between 2017 – 2021. Sample selected using purposive sampling. Data retrived from annual report dan proper rating report. Data analyzed using multiple regression method. The results of research are, envireomental performance has positive and significant effect on profitability and enviroenmental disclosure has no effect on profitability.